2017
DOI: 10.1007/978-3-319-66715-7_25
|View full text |Cite
|
Sign up to set email alerts
|

Masking Distracting Ambient Sound in an Adaptive VR-Application to Increase Presence

Abstract: The perception of disruptive outside sound while being inside a virtual reality simulation can break the experience of presence. Even with noise cancelling headphones external sound cannot be blocked completely. In this paper, we present an acoustic compensation method to sustain the virtual illusion. We developed a testbed VR prototype that allows to classify real-life sound and to adapt the virtual world accordingly by activating pre-defined playable content. The application analyzes and classifies outside s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…More details from the references of these studies are shown in Table 2. Reference Conclusion [96] The perception of disruptive outside sound while being inside a virtual reality simulation can break the experience of presence.…”
Section: Resultsmentioning
confidence: 99%
“…More details from the references of these studies are shown in Table 2. Reference Conclusion [96] The perception of disruptive outside sound while being inside a virtual reality simulation can break the experience of presence.…”
Section: Resultsmentioning
confidence: 99%